Is Curcumin an Antidote for Civilization Diseases? A Literature Review - Madej, Adrianna; Suława, Adrian; Targoński, Oskar; Targońska, Marta; Furgalska-Kudła , Julia; Fedorowicz, Sebastian; Basiak, Aneta; Ptasiński , Aleksander; Niekurzak, Rafał; Buczek, Agnieszka (Quality in Sport, 2024)
Introduction and purpose: Curcumin is the main natural lipophilic polyphenol obtained from Curcuma longa L. Its anti-inflammatory, anti-cancerous, anti-obesity, antioxidant, and lipid-lowering effects have attracted scientists' attention. Due to its diverse pharmacological properties, curcumin might be a beneficial and promising nutraceutical food dealing with civilization diseases. NCDs (non-communicable diseases) such as obesity, cardiovascular diseases, and diabetes mellitus are significant health issues affecting global society. Aim of the study: The purpose of this review is to present a thorough analysis of the impact of supplementation curcumin on the prevention, course, and complications of obesity, cardiovascular diseases, and diabetes mellitus. Material and methods: An analysis of papers available in PubMed and Google Scholar was performed using the following keywords: curcumin, curcumin and Type 2 Diabetes Mellitus, curcumin and chronic diseases, curcumin and obesity, curcumin and Cardiovascular diseases, curcumin and lipid, curcumin and glucose. Conclusion: As studies have shown, curcumin might be a promising nutraceutical food in treating obesity, cardiovascular diseases, and type 2 diabetes mellitus. Further research should be conducted to assess the impact of curcumin better and to establish the appropriate dose, formulation, and duration of the therapy.